2008
DOI: 10.1093/europace/eun335
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of conduction pathways to left atrium using magnetocardiography: validation by intra-cardiac electroanatomic mapping

Abstract: Magnetocardiographic mapping seems capable of distinguishing inter-atrial conduction pathways. Recognizing the inter-atrial conduction pattern may assist in understanding the pathogenesis of AF and identifying the subgroups for patient-tailored therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 36 publications
(48 reference statements)
3
31
0
Order By: Relevance
“…The MCG recordings and signal analyses were performed as previously described [9,11]. High-resolution MCG signals were recorded using a multi-channel cardiomagnetometer (Elekta Neuromag Ltd., Helsinki, Finland) equipped with 33 triple sensor dc-SQUID units on a slightly curved surface with a diameter of 30 cm.…”
Section: Magnetocardiographic Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The MCG recordings and signal analyses were performed as previously described [9,11]. High-resolution MCG signals were recorded using a multi-channel cardiomagnetometer (Elekta Neuromag Ltd., Helsinki, Finland) equipped with 33 triple sensor dc-SQUID units on a slightly curved surface with a diameter of 30 cm.…”
Section: Magnetocardiographic Methodsmentioning
confidence: 99%
“…The direction of the pseudocurrents points the direction of the source's activation over the inspected time interval. As a quantitative variable, the mean of the angles of the top 30% of the strongest pseudocurrents was used, zero angle direction pointing from subject's right to left and positive clockwise [9]. The atrial wave of each subject was allocated to one of the three predefined types: Type 1 with both early and later LA maps orienting leftward down, i.e., the pseudocurrent angle was positive during time interval of 40-70 ms from P wave onset and during later 50% of atrial signal; Type 2 with the map over the 40-70 ms orienting leftward down and the map over last 50% of atrial signal orienting leftward up, i.e., the pseudocurrent angle was positive and negative; and Type 3 with both maps orienting leftward up, i.e., the pseudocurrent angle was negative during both intervals (Fig.…”
Section: Magnetocardiographic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 27 patients undergoing catheter ablation of paroxysmal AF, MCG was recorded prior to determination of the LA activation sequence during sinus rhythm using invasive electroanatomical mapping. The MCG was able to identify three different pathways, the Bachmann bundle, the margin of the fossa ovalis, and the coronary sinus ostial region, as breakthrough of electrical activation from the right to the left atrium [58]. It could be further shown that susceptibility to paroxysmal lone AF is associated with propagation of the atrial signal to the LA via the margin of the fossa ovalis or multiple pathways.…”
Section: Rozkład Prądów Nasierdziowych U Pacjenta Z Ciasnym Zwężenimentioning
confidence: 96%